IoT-Based Household Electricity Usage Monitoring System Using Android - Yusuffi Yusuffi; Muhammad Fahmi; Ivan Haristyawan (STMIK Widya Cipta Dharma, 2026)
In daily life, uncontrolled electricity consumption can lead to the waste of electronic devices in households. Therefore, a system that is able to accurately monitor electricity use is needed. This study aims to find out how much electrical energy is used in households based on the Internet of Things (IoT) that can be accessed through android devices. The method used in this study is the prototype method. The system is built using a ESP8266 NodeMCU microcontroller connected to the internet network and a PZEM-004T sensor to measure the voltage, current, power, and electrical energy used. The result of this research is in the form of a monitoring tool that is able to display the use of electrical energy directly and can be monitored from anywhere through an android device. This system is expected to help the community in controlling electricity use to be more efficient.